2023
DOI: 10.3389/fmicb.2023.1279695
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing and analysis of Bacillus velezensis VJH504 reveal biocontrol mechanism against cucumber Fusarium wilt

Fan Yang,
Huayan Jiang,
Kai Ma
et al.

Abstract: One major issue in reducing cucumber yield is the destructive disease Cucumber (Cucumis sativus L.) wilt disease caused by Fusarium oxysporum f. sp. cucumerinum (Foc). When using the isolate VJH504 isolated from cucumber rhizosphere soil and identified as Bacillus velezensis, the growth of Foc in the double culture experiment was effectively inhibited. Phenotypic, phylogenetic, and genomic analyses were conducted to enhance understanding of its biocontrol mechanism. According to the result of the phenotype ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…B. velezensis could produce antimicrobial substances such as polyketides, lipopeptides, and peptides, which inhibit bacteria and fungi [21]. The secondary metabolites produced by B. velezensis involve bacillibactin, fengycin, bacilysin, surfactin, difficidin, and mersacidin, which exhibit broad antagonistic activities against pathogenic bacteria or fungi [22]. For example, anti-microbial substances such as bacillibactin chelated iron, fengycin altered cell wall permeability, bacilysin hindered glucosamine synthesis, surfactin destroyed cell membrane, and difficidin inhibited the protein biosynthesis of bacteria [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. velezensis could produce antimicrobial substances such as polyketides, lipopeptides, and peptides, which inhibit bacteria and fungi [21]. The secondary metabolites produced by B. velezensis involve bacillibactin, fengycin, bacilysin, surfactin, difficidin, and mersacidin, which exhibit broad antagonistic activities against pathogenic bacteria or fungi [22]. For example, anti-microbial substances such as bacillibactin chelated iron, fengycin altered cell wall permeability, bacilysin hindered glucosamine synthesis, surfactin destroyed cell membrane, and difficidin inhibited the protein biosynthesis of bacteria [23].…”
Section: Discussionmentioning
confidence: 99%
“…These secondary metabolites also induce systemic resistance in plants. Genome sequence analysis indicated that B. velezensis harbors many gene clusters encoding secondary metabolites, i.e., B. velezensis VJH504 contains several gene clusters encoding NRPS, transAT-PKS, T3PKS, and PKS-like types of secondary metabolites [22]; and B. velezensis HNA3 possesses 12 gene clusters related to 14 secondary metabolites with bioactive compounds [23]. Furthermore, B. velezensis shows high hydrolase activity due to the presence of protease, chitinase, cellulase, and glucanase, which is associated with carbon source and cellulose utilization [24].…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the Fusarium oxysporum f. sp. cucumerinum FJH36 ( Foc FJH36) fungi were isolated and conserved at the Institute of Horticulture, Henan Academy of Agricultural Sciences ( Yang et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…We measured plant height, stem diameter, leaf area, chlorophyll content, shoot fresh weight, root fresh weight, shoot dry weight and root dry weight on the 20th and 40th days during the whole growth period ( Yang et al, 2023 ; Figure 1D ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation